Application of lidar remote sensing of insects in agricultural entomology on the Chinese scene. (25th November 2019) - Song, Ziwei; Zhang, Baoxin; Feng, Hongqiang; Zhu, Shiming; Hu, Lingna; Brydegaard, Mikkel; Li, Yiyun; Jansson, Samuel; Malmqvist, Elin; Svanberg, Katarina; Zhao, Guangyu; Bood, Joakim; et al.
Abstract: Insect pest management is a very important aspect for plant protection in crops production. Remote sensing provides a large number of techniques that are beneficial in entomological research. Although entomological radars have been used for studying migrations of insects for many years, most of entomological radar studies have been vertically tracing high‐altitude migration behaviour of insects. Light detection and ranging (lidar) is a counterpart to radar, now operating in the optical part of the electromagnetic spectrum, which has been recently applied for monitoring of insects at low altitude. Such techniques, in particular low‐cost continuous‐wave (CW) bi‐static systems based on the Scheimpflug arrangement, have been rapidly developing during the last decade. As a result, optical methods present new and fascinating possibilities. Based on experience from a 2‐week field campaign in rice paddy fields, we here present an overview of lidar remote sensing applied to the Chinese scene. The capability of a CW Scheimpflug lidar system in monitoring the insects was studied. We present results on insect abundance in relation to time of the day and weather conditions. We also identified insect species by analysing wing‐beat frequencies and studied their attraction to ultraviolet (UV) lamp located close to the horizontal laser sampling path during night time. Results showed that the insect species were abundant, that insects detected by the lidar system were attracted to light and that light rain increased the insect activity. The lidar detection system had a high read‐out frequency, enabling the estimation of insect wing‐beat frequencies.